COVID-19 Outcomes Among Patients With Cancer: Observations From the University of California Cancer Consortium COVID-19 Project Outcomes Registry. (28th March 2022) - Borno, Hala T; Kim, Mi-Ok; Hong, Julian C; Yousefi, Sasha; Lin, Amy; Tolstykh, Irina; Zhang, Sylvia; McKay, Rana R; Harismendy, Olivier; Cinar, Pelin; Rugo, Hope; Koshkin, Vadim S; et al.
Abstract : The risks associated with COVID-19 in patients with cancer have not been fully characterized. Using data from the University of California Cancer COVID Consortium, this article evaluates outcomes associated with SARS-CoV-2 infection among patients with cancer. Abstract: Background: The risks associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its associated illness, coronavirus disease 2019 (COVID-19), among patients with a cancer diagnosis have not been fully characterized. This study leverages data from a multi-institutional cohort study, the University of California Cancer COVID Consortium, to evaluate outcomes associated with SARS-CoV-2 infection among patients with cancer. Methods: Clinical data were collected from March to November 2020 and included patient demographics, cancer history and treatment, SARS-CoV-2 exposure and testing, and COVID-19 clinical management and outcomes. Multivariate ordinal logistic regression permitting unequal slopes was used to evaluate the impact of demographic, disease, and treatment factors on SARS-CoV-2 related hospitalization, intensive care unit (ICU) admission, and mortality. Findings: Among all evaluated patients ( n = 303), 147 (48%) were male, 118 (29%) were older adults (≥65 years old), and 104 (34%) were non-Hispanic white. A subset ( n = 63, 21%) had hematologic malignancies and the remaining had solid tumors. Patients were hospitalized for acute care ( n = 79, 26%), ICU-level care ( n = 28, 9%), or died ( n = 21, 7%) due to COVID-19. Patients with ≥2 comorbidities were more likely to require acute care (odds ratio [OR] 2.09 [95% confidence interval (CI), 1.23-3.55]). Cough was identified as a significant predictor of ICU hospitalization (OR 2.16 [95% CI, 1.03-4.57]). Importantly, mortality was associated with an active cancer diagnosis (OR 3.64 [95% CI, 1.40-9.5]) or advanced age (OR 3.86 [95% CI, 1.2-12.44]). Interpretation: This study observed that patients with active cancer or advanced age are at an increased risk of death from COVID-19. These study observations can inform risk counseling related to COVID-19 for patients with a cancer diagnosis.